EFFECT OF MAGNETIC RESONANCE IMAGING IN THE DIAGNOSIS OF OVARIAN CANCER - Tairova M.I, Khayitboeva M.R., Bolunts E.A (Journal Park Publishing, 2023)
Due to the high contrast resolution, MRI is used to solve problems for sonographically indeterminate ovarian formations. To differentiate solid formations of appendages, high-quality diffusion-weighted MRI imaging is widely used, so that intravenous administration of a contrast agent can be avoided, which makes this technique indispensable in the presence of contraindications to contrast and during pregnancy.
Keywords: MRI, ovarian cancer, DVI, dermoid, ESUR.